Alcohol Problems, Jealousy, and Cyber Dating Abuse Perpetration Among Men and Women: Toward a Conceptual Model - Brem, Meagan J. (Journal of interpersonal violence, 2021)
Investigations of alcohol use in relation to cyber dating abuse (CDA) remain underdeveloped relative to alcohol-related face-to-face dating abuse research. A critical step toward advancing this area of research would include examining the applicability of alcohol-related partner abuse models to CDA perpetration. Existing models of alcohol-related partner abuse suggested that alcohol and partner abuse are more likely to co-occur in the presence of aggressogenic distal traits. We propose that this model may extend to CDA perpetration. Toward this end, the present study collected cross-sectional data from college students (N = 258; 56.2% male) to investigate whether trait romantic jealousy moderated the association between alcohol problems and CDA perpetration, controlling for face-to-face dating abuse perpetration. We hypothesized that alcohol problems would positively relate to CDA perpetration among college students with high, but not low, romantic jealousy. We explored whether the interactive effect varied by sex. Results revealed a significant three-way interaction; the moderating role of romantic jealousy in the relation between alcohol problems and CDA perpetration varied by sex. Alcohol problems positively related to CDA perpetration for women with high, but not low, romantic jealousy. Alcohol problems did not relate to CDA perpetration regardless of men’s level of romantic jealousy. These preliminary results suggested that alcohol-related partner abuse models may be useful for conceptualizing CDA perpetration and identifying CDA intervention components.